Secular and catastrophic processes reflected in sediments of the Suchedniów water reservoir, Holy Cross Mountains (Poland) - Przepióra, Paweł; Kalicki, Tomasz; Aksamit, Michał; Biesaga, Piotr; Frączek, Marcin; Grzeszczyk, Paulina; Malęga, Emanuela; Chrabąszcz, Mariusz; Kłusakiewicz, Edyta; Kusztal, Piotr (Geologos, 2019)
The Suchedniów water reservoir is located in the central section of the River Kamionka in the northern part of the Holy Cross Mountains of central Poland. This area once belonged to the Old Polish Industrial District that, during the Middle Ages, was very intensively developed by iron metallurgy. Many forges and mills along the rivers used water power, which led to the construction of an anthropogenic, small-scale water retention system. At the beginning of the twentieth century many of these reservoirs were drained after the collapse of metallurgical activities. The present-day reservoir was built in 1974 and drained in 2017. Research into the drained basin has documented various forms and sediments, some of which record present-day depositional processes (fire proof clay layer, inland fan delta), while others represent the historical period (lacustrine sediments of older reservoirs). Traces of catastrophic events have been preserved as well; an assemblage of megaripples marks the sudden drainage caused by a dam break in 1974.